Genomic Comparison of Lactobacillus casei AP and Lactobacillus plantarum DR131 with Emphasis on the Butyric Acid Biosynthetic Pathways - Widodo, Widodo (Microorganisms, 2021)
Butyric acid is known to possess anticarcinogenic and antioxidative properties. The local lactic acid bacteria (LAB) strains Lactobacillus casei AP isolated from the digestive tract of healthy Indonesian infants and L. plantarum DR131 from indigenous fermented buffalo milk (dadih) can produce butyric acid in vitro. However, the genes and metabolic pathways involved in this process remain unknown. We sequenced and assembled the 2.95-Mb L. casei AP and 4.44-Mb L. plantarum DR131 draft genome sequences. We observed that 98% of the 2870 protein-coding genes of L. casei AP and 97% of the 3069 protein-coding genes of L. plantarum DR131 were similar to those of an L. casei strain isolated from infant stools and an L. plantarum strain in sheep milk, respectively. Comparison of the genome sequences of L. casei AP and L. plantarum DR131 led to the identification of genes encoding butyrate kinase (buk) and phosphotransbutyrylase (ptb), enzymes involved in butyric acid synthesis in L. casei AP. In contrast, a medium-chain thio-esterase and type 2 fatty acid synthase facilitated butyric acid synthesis in L. plantarum DR131. Our results provide new insights into the physiological behavior of the two LAB strains to facilitate their use as probiotics.